Information literacy and Gen Z oversharing on Instagram - Ginting, Lisa Septia Dewi Br. (Universitas Jambi, Indonesia, 2025)
Abstract This study examined the relationship between information literacy and the oversharing behavior of Gen Z students’ outpourings on Instagram. The research was qualitative with an intrinsic case study approach, which allows for a holistic exploration of the experiences of the research subjects. Data were obtained through semi-structured interviews, online observations (netnography), and documentation of digital uploads of ten middle-level student informants who actively used Instagram. The thematic analysis results showed that low information literacy and unclear understanding of digital ethics made students vulnerable to impulsively sharing personal content. The need for social validation influenced this practice, as did social media cultural pressures and weak education about digital privacy, both in the family environment and educational institutions. This study highlighted the urgency of strengthening ethics-based digital literacy as a technical skill and a reflective competency to build wise and responsible digital behavior. These findings provide us with theoretical and practical contributions in developing contextual digital literacy education policies oriented towards the formation of the digital character of the young generation.